The Effect of Calligraphy on Career Decision-making Self-efficacy and Self-leadership of Nursing Students - Ko, Heesun; Lee, Hyunjung (International Journal of Membrane Science and Technology, 2023)
This is a single-arm pre-post study conducted to determine the effect of a calligraphy program on nursing students' career decision-making self-efficacy and self- leadership. The data collected from 231 second-year nursing students were analyzed using SPSS WIN 25.0 to determine descriptive statistics, paired t-test to analyze the effect of calligraphy, and Pearson correlation coefficient to determine the relationship between career decision self-efficacy and self-leadership. After the program, both career decision self-efficacy (t=7.23, p<.001) and self-leadership (t=6.81, p<.001) improved, and there were statistically significant differences in each of the sub-items. There was a difference in pre- and post-program self-efficacy based on satisfaction with their major, but the difference between groups was not significant on post-hoc tests. The analysis of career decision self-efficacy and self-leadership before the program showed a strong correlation (r=.811, p<.001) and a strong correlation after the program (r=.849, p<.001). The results of this study are significant in that they validate the effectiveness of a calligraphy program in promoting self-leadership and career decision-making self-efficacy among nursing students who do not have clear career goals. At a time when the importance of cultural arts education is gradually increasing in social and educational fields around the world, calligraphy has the advantage of laying the foundation for the promotion of basic arts for the revitalization of cultural arts, so educational support is needed not only in terms of improving the quality of life and pursuing self-actualization of individuals with emotional expression and creative problem-solving skills, but also at the social level.